Household Labor Supply Effects of Low-Wage Subsidies in Germany - Hilmar Schneider; Wolfram Kempe; Holger Bonin (Institute for the Study of Labor (IZA), 2002)
This research evaluates the impact on German household labor supply of various subsidy schemes proposed to foster low-wage employment. Using data from the German Socio-Economic Panel, we estimate a discrete choice model of household labor supply. On the basis of the estimated labor supply parameters of husbands and wives, we simulate participation and hours effects of different policies raising low labor earnings at the individual and household levels. In all cases, the labor supply effect is very moderate. Subsidies to individuals promote part-time employment, in particular of second earners, while subsidies based on low household income drive the better qualified partner out of the labor market so that the total number of labor market participants even declines.
Keywords: J68; J38; H24; J22; 330; low-wage subsidies; labor supply; discrete choice; Germany; Lohnsubvention; Niedriglohn; Haushaltsökonomik; Arbeitsangebot; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Privater Haushalt; Deutschland